Sperm Quality, Kinematics, Membrane Integrity, and DNA Fragmentation of Frozen Sexed Semen in Holstein-Friesian Bulls - F. Safa; A. P. A. Yekti; P. Utami; H. A. Syah; N. Febrianto; A. Rachmawati; A. Yuswati; A. Amaliya; D. Sulistyowati; T. Susilawati (Tropical Animal Science Journal)
Percoll density gradient centrifugation (PDGC) is a widely used method for sperm separation in Indonesia. This study evaluated sperm quality, membrane integrity, acrosome damage, and DNA fragmentation after PDGC-based sperm sexing and cryopreservation. This research was conducted as a laboratory experiment with six treatment groups: fresh semen (T1), post-sexing X-chromosome-bearing sperm (T2), post-sexing Y-chromosome-bearing sperm (T3), post-thawing unsexed semen (T4), post-thawing X-chromosome-bearing sperm (T5), and post-thawing Y-chromosome-bearing sperm (T6). The observed variables included individual motility (IM), viability, concentration, abnormality, total motile sperm (TMS), intact acrosome cap (IAC), membrane integrity (MI), DNA fragmentation, and sperm kinetic variables assessed using computer-assisted sperm analysis (CASA). The results showed that PDGC sexing significantly reduced IM, concentration, TMS, viability, MI, and IAC. Furthermore, the freezing of both unsexed and sexed semen further decreased IM, concentration, TMS, viability, MI, and IAC while increasing sperm abnormalities. DNA fragmentation increased post-sexing and freezing in unsexed semen, indicating potential DNA damage from these processes. Kinetic variable assessment using CASA showed that PDGC maintained sperm motility characteristics, whereas freezing led to a significant decline in sperm kinetics. In conclusion, PDGC is a viable method for sperm sexing in cattle, as it preserves sperm quality, membrane integrity, acrosome integrity, DNA integrity, and motility characteristics while being compatible with semen cryopreservation. These findings confirm that PDGC-processed semen is suitable for artificial insemination (AI).